On efficient solution of large-size wire-grid structures in a complex environment - Lee, Yee Hui. (2008)
In this study, four numerical techniques (1) wavelet transform method (WTM) (2) modified fast multipole method (MFMM) (3) adaptive segmentation method (ASM) (4) weak coupling suppression method (WCSM) for the efficient solution of large-size electromagnetic (EM) problems have been studied. These techniques have been implemented onto a popular simulation software - Numerical Electro-magnetic Code (NEC), which uses the method of moment (MoM) for the solution of EM problems in a complex environment. In the MoM, solving the impedance ma-trix equation becomes extremely computational time and memory intensive when the problem is large. Therefore, the main purpose of using these techniques is to break the bottle-neck existing in the MoM by either reducing the density or the order of the impedance matrix. In order to reduce the density of the impedance matrix, WTM and WCSM have been studied. Whereas MFMM and ASM are proposed and developed to reduce the order of the impedance matrix.